Memoirs 1910-1920 - Paderewska, Helena, 1856-1934; Siekierski, Maciej; Davies, Norman, 1939- (Stanford, California : Hoover Institution Press, 2015)
"These memoirs of Helena Paderewska, wife of the celebrated pianist Ignacy Jan Paderewsky, tell the story of her husband's grassroots efforts to influence the course of history for their native Poland after World War I. She tells how, using his personal fame and charisma, Paderewski gained access to the top political leadership of France, Britain, and the United States and became an eloquent spokesman for the then-occupied country of his birth."
Includes timeline, guide to names, and index.
Keywords: Paderewski, Ignace Jan, -- 1860-1941.; Paderewska, Helena, -- 1856-1934.; Statesmen -- Poland -- Biography; Pianists -- Poland -- Biography; Musicians' spouses -- Poland -- Biography